Zur Verbreitung von Informationen in sozialen Netzwerken - eine wirtschaftspolitische Analyse - Schulz, Hannah

Integrierte Entwicklung komplexer Systeme mit modellbasierter Systemspezifikation und -simulation - Roßmann, Jürgen; Schluse, Michael; Rast, Malte; Hoppen, Martin; Dumitrescu, Roman; Bremer, Christian; Hillebrand, Michael; Stern, Oliver; Blümel, Florian; Averdung, Christoph (Wissenschaftsforum Intelligente Technische Systeme (WinTeSys))

Approach for identifying components worthy of protection of Cyber-Physical Systems (CPS) based on a system model - Kliewe, Daniel; Kaiser, Lydia; Dumitrescu, Roman; Gausemeier, Jürgen (Jurnal Teknologi)

Implementing Model-Based Systems Engineering based on Shared Services - Concepts for Industrial Application - Bansmann, Michael; Tschirner, Christian; Dumitrescu, Roman (1st IEEE International Symposium on Systems Engineering (ISSE), Rome, Italy, 2015)

Why Fit Leads to Surprise: An Extension of Cognitive Fit Theory to Creative Problems - John, Thomas; Kundisch, Dennis (Proceedings of the 36th International Conference on Information Systems (ICIS), Fort Worth, USA)
Cognitive fit theory (CFT) provides guidance for how best to represent information that is relevant for solving a given problem. CFT is widely established in information systems research and its validity has been demonstrated in a great variety of contexts. However, of the two major types of problems that exist (i.e., routine and creative problems) prior CFT research has addressed only one: routine problems. Creative problems, despite their importance, have been left unaddressed. Therefore, based on the visual sketching model of problem solving, we propose an extension of CFT and thereby demonstrate that cognitive fit can promote problem solving performance also for creative problems. In doing so, we extend the boundary of CFT and add to creativity research a previously unknown cognitive mechanism for promoting creative performance: cognitive fit. Moreover, we contribute to general problem solving research by bridging the gap between problem solving in creativity and information systems research.

Feature Model Approach For Managing Variability of Dynamic Behavior Models in Mechatronic Systems - Abrishamchian, Farisoroosh; Oestersötebier, Felix; Trächtler, Ansgar (Proceedings of the ASME 2015 International Mechanical Engineering Congress & Exposition)

Decentralized Controller Reconﬁguration Strategies for Hybrid System Dynamics based on Product-Intelligence - Bertelsmeier, Fabian; Trächtler, Ansgar (20th IEEE International Conference on Emerging Technologies and Factory Automation)

Flexible Operation Workflow of a Driving Simulation Center for ADAS Development - Abdelgawad, Kareem; Hassan, Bassem; Kohlstedt, Andreas; Stöcklein, Jörg; Berssenbrügge, Jan; Grafe, Michael; Gausemeier, Sandra; Jäker, Karl-Peter; Trächtler, Ansgar (New Developments in Driving Simulation Design and Experiments)

ARTiST - An Augmented Reality Testbed for Intelligent Technical Systems - Hassan, Bassem; Stöcklein, Jörg; Berssenbrügge, Jan (Virtual, Augmented and Mixed Reality VAMR 2015 Held as Part of HCI International 2015)

Visualization of Headlight Illumination for the Virtual Prototyping of Light-Based Driver Assistance Systems - Berssenbrügge, Jan; Trächtler, Ansgar; Schmidt, Christoph (Proceedings of the ASME 2015 International Design Engineering Technical Conferences & Computers and Information in Engineering Conference)

Parametrische Modellordnungsreduktion für hierarchische selbstoptimierende Systeme - Krüger, Martin; Trächtler, Ansgar (at-Automatisierungstechnik)

Produkt- und lastabhängiges dezentrales Motormanagement für die Fördertechnik: Anforderungen, Design und Applikation - Bertelsmeier, Fabian; Vathauer, Marc; Henke, Christian; Vathauer, Karl-Ernst; Trächtler, Ansgar (Automation 2015)

Modelling the Constitutive Behaviour of Martensite and Austenite in Shape Memory Alloys Using Closed-Form Analytical Continuous Equations - Pai, Arathi; Niendorf, Thomas; Krooß, Philipp; Koke, Isabel; Trächtler, Ansgar; Schaper, Mirko (7th ECCOMAS Thematic Conference on Smart Structures and Materials - SMART)

Intelligente Biegeverfahren - Damerow, Ulf-Hendrik; Borsig, Michael; Tabakajew, Dmitri; Schaermann, Waldemar; Hesse, Marc; Homberg, Werner; Trächtler, Ansgar; Jungeblut, Thorsten (wt Werkstattstechnik online)

A Modular Architecture of an Interactive Simulation and Training Environment for Advanced Driver Assistance Systems - Abdelgawad, Kareem; Hassan, Bassem; Berssenbrügge, Jan; Stöcklein, Jörg; Grafe, Michael (International Journal On Advances in Software)

Design and Control of Cooperative Ball Juggling Delta Robots without Visual Guidance - Shareef, Zeeshan; Just, Viktor; Teichrieb, Heinrich; Trächtler, Ansgar (Robotica)

Path Planning and Trajectory Optimization of Delta Parallel Robot - Shareef, Zeeshan

Automatische Ableitung geometrischer Eigenschaften von Bauteilen aus dem 3-D-Polygonmodell - Jähn, Claudius; Fischer, Matthias; Gerges, Maria; Berssenbrügge, Jan (12. Paderborner Workshop Augmented & Virtual Reality in der Produktentstehung)

Visualisierung von Scheinwerfersystemen für das Virtual Prototyping von lichtbasierten Fahrerassistenzsystemen - Berssenbrügge, Jan; Trächtler, Ansgar; Schmidt, Christoph; Stöcklein, Jörg; Grafe, Michael (12. Paderborner Workshop Augmented & Virtual Reality in der Produktentstehung)

Anbindung des Virtuellen Prototypen an die Partialmodelle intelligenter technischer Systeme - Berssenbrügge, Jan; Wiederkehr, Olga; Jähn, Claudius; Fischer, Matthias (12. Paderborner Workshop Augmented & Virtual Reality in der Produktentstehung)

Entwicklung eines prädiktiven Motion-Cueing-Verfahrens für den ATMOS-Fahrsimulator - Zimmermann, Daniel; Kohlstedt, Andreas; Gausemeier, Sandra; Trächtler, Ansgar (12. Paderborner Workshop Augmented & Virtual Reality in der Produktentstehung)

Online-Rekonﬁguration hybrider Regelkreise in Abhängigkeit variierender Produkteigenschaften - Bertelsmeier, Fabian; Engelmeier, Tobias; Trächtler, Ansgar (Tagungsband Mechatronik 2015)

Systematische Wahl der Modellierungstiefe im Entwurfsprozess mechatronischer Systeme am Beispiel eines Geldautomaten - Lochbichler, Matthias; Lankeit, Christopher; Trächtler, Ansgar; Landwehr, Martin; Hoischen, Ludger (Tagungsband Mechatronik)

Tutorenprogramm und Vertiefungsberatung stellen Weichen in entscheidenden Phasen des Student Life-Cycles in Maschinenbaustudiengängen - Koke, Isabel; Dibblee, Katharina; Hankeln, Frederik; Seidel, Stefan; Trächtler, Ansgar; Schmid, Hans-Joachim (44. Jahrestagung der Deutschen Gesellschaft für Hochschuldidaktik - Hochschuldidaktik im Dialog, Paderborn)

Modellbasierte Mehrzieloptimierung zur Integration von Hausgeräten in SmartGrids - Michael, Jan; Hillebrand, Michael; Dumitrescu, Roman; Henke, Christian; Trächtler, Ansgar (VDI Mechatronik 2015 Tagungsband)

Safe trajectory planning for autonomous intersection management by using vehicle to infrastructure communication - Wuthishuwong, Chairit; Trächtler, Ansgar; Bruns, Torsten (EURASIP Journal on Wireless Communications and Networking)

Challenges in Requirements Engineering for Mechatronic Systems – Problem Analysis and First Approach - Lankeit, Christopher; Lochbichler, Matthias; Trächtler, Ansgar (Jurnal Teknologi)

From Goals to Systems via Technical Requirements and Physical Models - Design of an Intelligent Cash Handling System - Lankeit, Christopher; Lochbichler, Matthias; Oestersötebier, Felix; Trächtler, Ansgar; Landwehr, Martin (Proceedings)

Real-Time Compatible Phenomenological Modelling of the Austenitic Phase in Shape Memory Alloys as an Example for Modelling of Materials with Repeatable Non-Linear Characteristics - Pai, Arathi; Trächtler, Ansgar; Schaper, Mirko (IFAC 1st Conference on Modelling, Identification and Control of Nonlinear Systems - MICNON)

What did you mean? Facing the Challenges of User-generated Software Requirements - Geierhos, Michaela; Schulze, Sabine; Bäumer, Frederik Simon (Proceedings of the 7th International Conference on Agents and Artificial Intelligence (ICAART), Special Session on Partiality, Underspecification, and Natural Language Processing (PUaNLP 2015))
Existing approaches towards service composition demand requirements of the customers in terms of service templates, service query profiles, or partial process models. However, addressed non-expert customers may be unable to fill-in the slots of service templates as requested or to describe, for example, pre- and postconditions, or even have difficulties in formalizing their requirements. Thus, our idea is to provide non-experts with suggestions how to complete or clarify their requirement descriptions written in natural language. Two main issues have to be tackled: (1) partial or full inability (incapacity) of non-experts to specify their requirements correctly in formal and precise ways, and (2) problems in text analysis due to fuzziness in natural language. We present ideas how to face these challenges by means of requirement disambiguation and completion. Therefore, we conduct ontology-based requirement extraction and similarity retrieval based on requirement descriptions that are gathered from App marketplaces. The innovative aspect of our work is that we support users without expert knowledge in writing their requirements by simultaneously resolving ambiguity, vagueness, and underspecification in natural language.

Weighted Boolean Formula Games - Monien, Burkhard; Mavronicolas, Marios; Wagner, Klaus (the ´Festschrift´ Algorithms, Probability, Networks, and Games: Scientific Papers and Essays Dedicated to Paul G. Spirakis on the Occasion of His 60th Birthday)
We introduce weighted boolean formula games (WBFG) as a new class of succinct games. Each player has a set of boolean formulas she wants to get satisfied; the formulas involve a ground set of boolean variables each of which is controlled by some player. The payoff of a player is a weighted sum of the values of her formulas. We consider both pure equilibria and their refinement of payoff-dominant equilibria [34], where every player is no worse-off than in any other pure equilibrium. We present both structural and complexity results:We consider mutual weighted boolean formula games (MWBFG), a subclass of WBFG making a natural mutuality assumption on the formulas of players. We present a very simple exact potential for MWBFG. We establish a polynomial monomorphism from certain classes of weighted congestion games to subclasses of WBFG and MWBFG, respectively, indicating their rich structure.We present a collection of complexity results about decision (and search) problems for both pure and payoff-dominant equilibria in WBFG. The precise complexities depend crucially on five parameters: (i) the number of players; (ii) the number of variables per player; (iii) the number of formulas per player; (iv) the weights in the payoff functions (whether identical or not), and (v) the syntax of the formulas. These results imply that, unless the polynomial hierarchy collapses, decision (and search) problems for payoff-dominant equilibria are harde than for pure equilibria.

Voronoi Cells of Lattices with Respect to Arbitrary Norms - Blömer, Johannes; Kohn, Kathlén
Motivated by the deterministic single exponential time algorithm of Micciancio and Voulgaris for solving the shortest and closest vector problem for the Euclidean norm, we study the geometry and complexity of Voronoi cells of lattices with respect to arbitrary norms.On the positive side, we show that for strictly convex and smooth norms the geometry of Voronoi cells of lattices in any dimension is similar to the Euclidean case, i.e., the Voronoi cells are defined by the so-called Voronoi-relevant vectors and the facets of a Voronoi cell are in one-to-one correspondence with these vectors. On the negative side, we show that combinatorially Voronoi cells for arbitrary strictly convex and smooth norms are much more complicated than in the Euclidean case.In particular, we construct a family of three-dimensional lattices whose number of Voronoi-relevant vectors with respect to the l_3-norm is unbounded.Since the algorithm of Micciancio and Voulgaris and its run time analysis crucially dependonthefactthatfortheEuclidean normthenumber of Voronoi-relevant vectors is single exponential in the lattice dimension, this indicates that the techniques of Micciancio and Voulgaris cannot be extended to achieve deterministic single exponential time algorithms for lattice problems with respect to arbitrary l_p-norms.

Towards a sustainable and economic selection of part candidates for Additive Manufacturing - Lindemann, C.; Jahnke, U.; Reiher, T.; Koch, R. (Rapid Prototyping Journal)
Purpose – This paper aims to present a methodology to help end-users to find appropriate part candidates for the use of the additive manufacturing (AM) technology. These shall be capable of bringing AM into their businesses. The concept furthermore includes approaches for redesigning current available parts and helps to estimate the economic implications of the use of the technology. Design/methodology/approach – The approach starts to discuss general economic aspects for the successful use of AM. While describing the introduction of new technologies into existing businesses, the importance of an appropriate part selection for AM is pointed out. A methodology for a part selection process is presented, and the different criteria are developed. An approach for a redesign of the selected parts, including the gathering of requirements, is given based on different sample parts. A variation of criteria to include measures for product piracy is highlighted. Findings – The methodology has proven applicability in several research and industry projects in aerospace applications. Independent part selections from experts analyzed within a project of the European Space Agency had a 90 per cent overlap with the results. It allows companies with only basic AM knowledge to start a part screening for applicable AM candidates in their own company with a reasonable effort. Originality/value – The methodology for the redesign process helps to identify the main functions of the products targeted and the relevant environment, so one can benefit from the various advantages that AM has to offer. The selection methodology helps to ask the right questions and to reduce the effort.

Developement of an economic decision support for the application of Additive Manufacturing in aerospace - Deppe, G.; Lindemann, C.; Koch, R. (26th Annual International Solid Freeform Fabrication Symposium)
Additive Manufacturing offers a high potential in aerospace industry due to its freedom of design and the ability to manufacture complex and lightweight parts. The low number of units, high quality standards and fast response time are special challenges that have to be met especially in the Maintenance, Repair and Overhaul sector. Thus, companies have to decide at which point it is economic to apply Additive Manufacturing. However, companies lack experience on this new technology. This is why a tool is required that takes into account the above mentioned crucial points and supports the decision process. The paper analyzes aviation’s characteristics with regard to Additive Manufacturing. The structure of current MRO repair workflows is investigated to identify a feasible application for Additive Manufacturing. Additionally the supply chain will be examined to indicate the benefit which the technology can generate in this highly demanding field. The findings are integrated into a methodology that supports the decision whether to apply Additive Manufacturing on the basis of costs, time and quality.

Protection measures against product piracy and application by the use of AM - Jahnke, U.; Büsching, J.; Reiher, T.; Koch, R. (26th Annual International Solid Freeform Fabrication Symposium)
Presently the implications Additive Manufacturing (AM) on intellectual properties are discussed in public. Here AM is often mentioned as a driver for product piracy as it allows to produce and to copy objects with any geometries. Imitators need a lot of information to copy an object accurately. As reverse engineering has been identified as the most important information source for product imitators, AM can also help to reduce the threat of product piracy when correctly applied in the product development. Due to the layer wise production process that allows the manufacturing of very complex shapes and geometries, the reverse-engineering process can be complicated by far. By this, quite contrary to the public opinion, AM can increase the needed effort of imitators and strongly reduce the economic efficiency of product piracy. This paper will show different protection measures and a methodological approach of how to apply these measures to a product. Beside the protective effect some measures allow a traceability of parts over the product’s lifecycle and thus support the quality management of AM processes and additively produced parts.

FE-Optimization and data handling for Additive Manufacturing of structural parts - Reiher, T.; Koch, R. (26th Annual International Solid Freeform Fabrication Symposium)
Additive Manufacturing (AM) offers high potential due to its freedom of design for structural parts. Especially in combination with FE-based topology optimization an optimal use of material and thus significant weight reductions can be expected. However, the application of AM is hampered by different additional manufacturing processes along the entire production chain and data handling induced restrictions.Disadvantages emerge from a lack of adjustment of the entire design process for AM. First the optimization algorithms are not targeted to the opportunities and restrictions of AM –represented by design rules – like the design of support structures. Secondly, the CAD software is not adjusted to AM in particular. Creating freeform shaped surfaces based on the optimization results is significantly less convenient than building defined blocks or turning parts following the needs of conventional machining. The indispensable subsequent interpretation of optimization results regarding the design rules and the possibilities of CAD-tools counteracts optimal results. This paper considers different approaches for a Topology Optimization (TO)-shape regaining on different sample parts including telecommunication satellite parts. An innovative design methodology is presented getting crucial for creating high quality designs.

Sustainable Part Selection for the Use of Additive Manufacturing in Companies Focussing on Prevention of Product Piracy - Jahnke, U.; Lindemann, C. (Inside 3D Printing Conference and Expo)

Exploring the cost and lifetime benefits of a topology optimized aerospace part applying additive manufacturing - Deppe, G.; Reiher, T.; Koch, R. (International Conference Production Engineering and Management 2015)
The aerospace sector is characterized by long product life cycles and a need for lightweight design. Additive manufacturing is a technology that produces parts layer by layer and thus enables the manufacturing of any complex parts at nearly no extra costs. A topology optimization enhances the part’s performance for their special purpose. The results are often complex bionic structures that cannot be produced with conventional manufacturing technologies. The paper analyzes how the high potential of this technology can be applied to aerospace parts. A topology optimization will be conducted for an aircraft part explaining the crucial points and a life cycle analysis examines the achieved sustainable improvements for the aircraft’s life cycle.

Guidelines for a sustainable and economic selection of part candidates for space applications using additive manufacturing - Lindemann, C.; Reiher, T.; Koch, R. (Paris Space Week)

In-Class Exercise for Shadow Mapping Algorithms - Wiens, Alex; Domik, Gitta (IEEE Computer Graphics and Applications)

In-Class Exercises for Shadow Volume Algorithms - Wiens, Alex; Domik, Gitta (IEEE Computer Graphics and Applications)

Future Directions in Computer Graphics and Visualization: From CG&A's Editorial Board - Encarnacao, L. M.; Chuang, Y.; Stork, A.; Kasik, D.; Rhyne, T.; Avila, L.; Kohlhammer, J.; LaViola, J.; Tory, M.; Dill, J.; Domik, Gitta; Owen, G. S.; et al. (IEEE Computer Graphics and Applications)

Hypoplastic left heart in the 6500-year-old Detmold Child - Haas, Nikolaus; Zelle, Michael; Rosendahl, Wilfried; Zink, Albert; Preuss, Rainer; Laser, Kai; Gostner, Paul; Arens, Stephan; Domik, Gitta; Burchert, Wolfgang (Lancet (London, England))

Teaching Information Aesthetics as a Research Class in China - Zhang, K.; Nguyen , Q. V.; Meng , Z.; Tao, W. (IEEE Computer Graphics and Applications)

Preparing Undergraduates for Visual Analytics - Rensink, R. A. (IEEE Computer Graphics and Applications)

Evaluating and Grading Students in Large-Scale Image Processing Courses - Artner, N. M.; Janusch, I.; Kropatsch, W.G. (IEEE Computer Graphics and Applications)

Educational Virtual-Wear Trial: More Than a Virtual Try-On Experience - Cao, Mingliang; Li, Yi; Pan, Zhigeng; Csete, Josephine; Sun, Shu; Li, Jie; Liu, Y.u (IEEE Computer Graphics and Applications)

Zur affektiv-motivationalen Entwicklung von Lernenden im bilingualen Sachfachunterricht - Rumlich, Dominik (CLIL Revisited: Eine kritische Analyse des gegenwärtigen Standes des bilingualen Sachfachunterrichts)

Selbst(bestimmt) sind die Lernenden! Ideen und Methoden für eine studierendenzentrierte Lernveranstaltung. - Rumlich, Dominik (Diversität konkret)

Analysis and Optimization of the Dimensional Accuracy for FDM Parts manufactured with ABS-M30 - Knoop, F.; Schöppner, Volker (ASPE Spring Topical Meeting)

Mechanical and Thermal Properties of FDM Parts manufactured with Polyamide 12 - Knoop, F.; Schöppner, Volker (26th Annual International Solid Freeform Fabrication Symposium)
Fused Deposition Modeling (FDM) is an Additive Manufacturing (AM) technology which is used for prototypes, single-part production and also small batch productions. For use as a final product, it is important that the parts have good mechanical properties, high dimensional accuracy and smooth surfaces. The knowledge of the mechanical properties is very important for the design engineer when it comes to the component design. End-use products out of the FDM process have to resist applied forces. In this paper, investigations were conducted with the polymer Polyamide 12 (FDM Nylon 12) from Stratasys Inc. This polymer can be processed with three different tip sizes resulting in different layer thicknesses from 178 µm to 330 µm. Thus, the mechanical properties were determined for these layer thicknesses and for different orientations on the build platform. In addition to the mechanical properties the thermal properties (e.g. with a DSC analysis) are also investigated.

You Might Want to Engage Your Customers, But Choose Them Wisely: The Mixed Effects of Company-Initiated Customer Engagement on Customer Loyalty - Eggert, A; Steinhoff, L; Witte, C (2015 AMA Summer Marketing Educators' Conference Proceedings)

Stock Market Reactions to Business Service Outsourcing in Manufacturing Firms - Cramer, C; Böhm, E; Eggert, A (Proceedings of the 44th European Marketing Academy (EMAC) Conference)

Threatening customers not to return – An effective strategy for online retailers? - Feider, L; Garnefeld, I; Böhm, E (Proceedings of the 44th European Marketing Academy (EMAC) Conference)

Projektmanagement und Vorgehensmodelle 2015: Hybride Projektstrukturen erfolgreich umsetzen - Proceedings der gemeinsamen Tagung der Fachgruppen WI-PM und WI-VM im Fachgebiet Wirtschaftsinformatik der Gesellschaft für Informatik e.V.

Tickets without Fine - Artifact-based Synchronization of Globally Distributed Software Development in Practice - Fazal-Baqaie, Masud; Grieger, Marvin; Sauer, Stefan (Proceedings of the 16th International Conference of Product Focused Software Development and Process Improvement (PROFES 2015))

Successfully Initiating a Global Software Project - Fazal-Baqaie, Masud; Raninen, Anu (Industrial Proceedings of the 22nd European Systems Software & Service Process Improvement & Innovation Conference (EuroSPI²2015))

Kooperative Methoden- und Werkzeugentwicklung zur Cloudmigration von proprietären Anwendungskomponenten - Nagel, Benjamin; Schröder, Klaus; Becker, Steffen; Sauer, Stefan; Engels, Gregor (Software Engineering & Management 2015)
Die cloudbasierte Bereitstellung von Funktionen als Software-as-a-Service (SaaS) ermöglicht die Erschließung neuer Kundenpotenziale bei kleinen und mittelgroßen Unternehmen.

High-Performance Computing for Scheduling Decision Support: A Parallel Depth-First Search Heuristic - Rauchecker, Gerhard; Schryen, Guido (Australasian Conference on Information Systems)
Many academic disciplines - including information systems, computer science, and operations management - face scheduling problems as important decision making tasks. Since many scheduling problems are NP-hard in the strong sense, there is a need for developing solution heuristics. For scheduling problems with setup times on unrelated parallel machines, there is limited research on solution methods and to the best of our knowledge, parallel computer architectures have not yet been taken advantage of. We address this gap by proposing and implementing a new solution heuristic and by testing different parallelization strategies. In our computational experiments, we show that our heuristic calculates near-optimal solutions even for large instances and that computing time can be reduced substantially by our parallelization approach.
Keywords: scheduling; decision support; heuristic; high performance computing; parallel algorithms

Revenue Management for Cloud Computing Providers: Decision Models for Service Admission Control under Non-probabilistic Uncertainty - Püschel, Tim; Schryen, Guido; Hristova, Diana; Neumann, Dirk (European Journal of Operational Research)
Cloud computing promises the flexible delivery of computing services in a pay-as-you-go manner. It allows customers to easily scale their infrastructure and save on the overall cost of operation. However Cloud service offerings can only thrive if customers are satisfied with service performance. Allow-ing instantaneous access and flexible scaling while maintaining the service levels and offering competitive prices poses a significant challenge to Cloud Computing providers. Furthermore services will remain available in the long run only if this business generates a stable revenue stream. To address these challenges we introduce novel policy-based service admission control mod-els that aim at maximizing the revenue of Cloud providers while taking in-formational uncertainty regarding resource requirements into account. Our evaluation shows that policy-based approaches statistically significantly out-perform first come first serve approaches, which are still state of the art. Furthermore the results give insights in how and to what extent uncertainty has a negative impact on revenue.
Keywords: admission control; informational uncertainty; revenue management; cloud computing

Futurizing” Smart Service: Implications for Service Researchers and Managers. - Wünderlich, Nancy; Heinonen, Kristina; Ostrom, Amy L; Patricio, Lia; Sousa, Rui; Voss, Chris; Lemmink, Jos (Journal of Services Marketing)
Purpose – The purpose of this paper is to craft a future research agenda to advance smart service research and practice. Smart services are delivered to or via intelligent objects that feature awareness and connectivity. For service researchers and managers, one of the most fascinating aspects of smart service provision is that the connected object is able to sense its own condition and its surroundings and thus allows for real-time data collection, continuous communication and interactive feedback. Design/methodology/approach – This article is based on discussions in the workshop on “Fresh perspectives on technology in service” at the International Network of Service Researchers on September 26, 2014 at CTF, Karlstad, Sweden. The paper summarizes the discussion on smart services, adds an extensive literature review, provides examples from business practice and develops a structured approach to new research avenues. Findings – We propose that smart services vary on their individual level of autonomous decision-making, visibility and embeddedness in objects and customer lives. Based on a discussion of these characteristics, we identify research avenues regarding the perception and nature of smart services, the adoption of smart services, the innovation through smart services as well as regarding the development of new business models. Originality/value – Smart services is a new emerging topic in service marketing research, their implications on organizations, customers and the service landscape have not been fully explored. We provide a fresh perspective on service research by characterizing relevant aspects of smart service that will stimulate fruitful future research and advance the understanding and practice of smart services.
Keywords: Connected services; Intelligent object; New service type; Smart services

Conducting Service Research that Matters. - Gustafsson, Anders; Aksoy, Lerzan; Brady, Michael K; McColl-Kennedy, Janet R; Sirianni, Nancy J; Witell, Lars; Wünderlich, Nancy (Journal of Services Marketing)
Purpose – The purpose of this paper is to encourage the reader to think differently about service-related issues and to strive to conduct service research that makes a transformational impact on individuals, organizations and society. The authors suggest that service researchers are in an excellent position to develop research that matters by making stronger connections with theory and elevating purely applied research to research that is higher in both practical relevance and methodological rigor. Design/methodology/approach – This paper takes a conceptual approach, connecting pertinent literature with new ideas highlighted in this special issue. Findings – This paper proposes that service researchers look beyond traditional service applications, take a multi-disciplinary approach to problem-solving and make greater strides towards connecting theory and practice. The authors propose a Model of Rigorous and Relevant Research, and call for fresh thinking across a wide range of research areas, including enhancing the customer experience, crafting innovation, integrating technology and measuring service outcomes. Originality/value – The originality of this essay lies in its focus on revitalizing the discussion on relevance and rigor as a path forward for service research. Additionally, this paper offers new insights on core management aspects of service provision that provide a solid platform for future work in service research.
Keywords: Relevance; Service technology; Service innovation; Customer experience; Rigor; Service outcomes

The Value of Self-Service: Long-Term Effects of Technology-Based Self-Service Usage on Customer Retention. - Scherer, Anne; Wünderlich, Nancy; Von Wangenheim, Florian (MIS Quarterly)
Advancements in information technology have changed the way customers experience a service encounter and their relationship with service providers. Especially technology-based self-service channels have found their way into the 21st century service economy. While research embraces these channels for their cost-efficiency, it has not examined whether a shift from personal to self-service affects customer–firm relationships. Drawing from the service-dominant logic and its central concept of value-in-context, we discuss customers’ value creation in self-service and personal service channels and examine the long-term impact of these channels on customer retention. Using longitudinal customer data, we investigate how the ratio of self-service versus personal service use influences customer defection over time. Our findings suggest that the ratio of self-service to personal service used affects customer defection in a U-shaped manner, with intermediate levels of both self-service and personal service use being associated with the lowest likelihood of defection. We also find that this effect mitigates over time. We conclude that firms should not shift customers toward self-service channels completely, especially not at the beginning of a relationship. Our study underlines the importance of understanding when and how self-service technologies create valuable customer experiences and stresses the notion of actively managing customers’ cocreation of value.
Keywords: customer defection; customer retention; e-service; longitudinal; Self-service; value-in-context

Advancing Research on Loyalty Programs: A Future Research Agenda. - Breugelmans, Els; Bijmolt, Tammo H A; Zhang, Jie; Basso, Leonardo J; Dorotic, Matilda; Kopalle, Praveen; Minnema, Alec; Mijnlieff, Willem Jan; Wünderlich, Nancy (Marketing Letters)
Despite the growing literature on loyalty program (LP) research, many questions remain underexplored. Driven by advancements in information technology, marketing analytics, and consumer interface platforms (e.g., mobile devices), there have been many recent developments in LP practices around the world. They impose new challenges and create exciting opportunities for future LP research. The main objective of this paper is to identify missing links in the literature and to craft a future research agenda to advance LP research and practice. Our discussion focuses on three key areas: (1) LP designs, (2) Assessment of LP performance, and (3) Emerging trends and the impact of new technologies. We highlight several gaps in the literature and outline research opportunities in each area.
Keywords: Loyalty programs; Loyalty program design; Loyalty program performance assessment; Emerging trends; Partnership loyalty programs; Customer relationship management

A vulnerability's lifetime - Glanz, Leonid; Schmidt, Sebastian; Wollny, Sebastian; Hermann, Ben (Proceedings of the 15th International Conference on Knowledge Technologies and Data-driven Business - i-KNOW '15)

Design your analysis: a case study on implementation reusability of data-flow functions - Lerch, Johannes; Hermann, Ben (Proceedings of the 4th ACM SIGPLAN International Workshop on State Of the Art in Program Analysis - SOAP 2015)

Getting to know you: towards a capability model for Java - Hermann, Ben; Reif, Michael; Eichberg, Michael; Mezini, Mira (Proceedings of the 2015 10th Joint Meeting on Foundations of Software Engineering - ESEC/FSE 2015)

Hidden truths in dead software paths - Eichberg, Michael; Hermann, Ben; Mezini, Mira; Glanz, Leonid (Proceedings of the 2015 10th Joint Meeting on Foundations of Software Engineering - ESEC/FSE 2015)

Model-driven UI Development Integrating HCI Patterns - Yigitbas, Enes; Mohrmann, Bastian; Sauer, Stefan (Proceedings of the 1st Workshop on Large-scale and Model-based Interactive Systems: Approaches and Challenges, LMIS 2015, co-located with 7th ACM SIGCHI Symposium on Engineering Interactive Computing Systems {(EICS} 2015), Duisburg, Germany, June 23, 2015.)

A Model-Based Framework for Multi-Adaptive Migratory User Interfaces - Yigitbas, Enes; Sauer, Stefan; Engels, Gregor (Human-Computer Interaction: Interaction Technologies - 17th International Conference, HCI International 2015, Los Angeles, CA, USA, August 2-7, 2015, Proceedings, Part II)

Bilateral matching and bargaining games - Mikroökonomie, Lehrstuhl

First Steps towards a Tool Chain for Automatic Processing of Multimodal Corpora - Menke, Peter; Freigang, Farina; Kronenberg, Thomas; Klett, Sören; Bergmann, Kirsten (Journal of Multimodal Communication Studies)

Komplexe Selbstlernaufgabe (,WiWi-Studies') in der Eingangsphase wirtschaftswissenschaftlicher Bachelorstudiengänge. Einblicke in ein Design-Based Research-Projekt mit Studierendenbefragungen - Zoyke, A.; Kremer, H.-Hugo; Sampaio-Araujo, J. (Kölner Zeitschrift für Wirtschaft und Pädagogik)

Integrating Human-Centered and Model-Driven Methods in Agile UI Development - Fischer, Holger Gerhard; Yigitbas, Enes; Sauer, Stefan (Proceedings of 15th IFIP TC.13 International Conference on Human-Computer Interaction (INTERACT))

What does Vocational Mean? Exploring the Understanding of Vocational in Higher Education and Vocational Education - Kremer, H.-Hugo; Rüschen, E. (Crossing Boundaries in Vocational Education and Training: Innovative Concepts for the 21st Century. Conference Proceedings)

Qualitätsdimensionen für interaktive Systeme - Stand der Arbeiten UPA AK Qualitätsstandards - Fischer, Holger Gerhard; Polkehn, Knut; Geis, Thomas; Kluge, Oliver; Behrenbruch, Kay; Riedemann, Catharina (Mensch und Computer 2015 - Usability Professionals)

Gestaltung der Studieneingangsphase an einer wirtschaftswissenschaftlichen Fakultät - Kerbs, N.; Kremer, H.-Hugo; Rüschen, E.; Sampaio-Araujo, J.; Zoyke, A. (Das Hochschulwesen)

Individuelle Kompetenzentwicklungswege: Bildungsarbeit in einer dualisierten Ausbildungsvorbereitung: Das Forschungs- und Entwicklungsprojekt InBig - Beutner, Marc; Kremer, H.-Hugo; Kundisch, Heike; Rohde, S.; Zoyke, A. (Individuelle Kompetenzentwicklungswege: Bildungsarbeit in einer dualisierten Ausbildungsvorbereitung. Ergebnisse und Reflexionen aus dem Forschungs- und Entwicklungsprojekt InBig)

Überlegungen zur Modellierung der Bildungsarbeit im Rahmen von InBig - Kremer, H.-Hugo; Zoyke, A. (Individuelle Kompetenzentwicklungswege: Bildungsarbeit in einer dualisierten Ausbildungsvorbereitung. Ergebnisse und Reflexionen aus dem Forschungs- und Enwticklungsprojekt InBig)

Bildungsgangarbeit an Berufskollegs. Diskussionsbericht zur Bestandserhebung an den Pilot-Berufskollegs im Projekt InBig - Kranert, T.; Kremer, H.-Hugo; Zoyke, A. (Individuelle Kompetenzentwicklungswege: Bildungsarbeit in einer dualisierten Ausbildungsvorbereitung. Ergebnisse und Reflexionen aus dem Forschungs- und Entwicklungsprojekt InBig)

Mensch und Computer 2015 - Usability Professionals. Tagungsband

Grundstrukturen und Arbeitsbasis - Zur Entwicklung der Standortkonzepte - InBig als Forschungsfrage und Entwicklungsarena - Kremer, H.-Hugo; Beutner, Marc; Kranert, T. (Individuelle Kompetenzentwicklungswege: Bildungsgangarbeit in einer dualisierten Ausbildungsvorbereitung. Ergebnisse und Reflexionen aus dem Forschungs- und Entwicklungsprojekt InBig)

Kurzportrait zum Standortkonzept des Robert-Bosch-Berufskolleg der Stadt Dortmund - Rose, S.; Kranert, T.; Kremer, H.-Hugo (Individuelle Kompetenzentwicklungswege: Bildungsgangarbeit in einer dualisierten Ausbildungsvorbereitung. Ergebnisse und Reflexionen aus dem Forschungs- und Entwicklungsprojekt InBig)

Kurzportrait zum Standortkonzept des Berufskollegs Ernährung, Sozialwesen, Technik in Geilenkirchen - Beutner, Marc; Kranert, T.; Kremer, H.-Hugo (Individuelle Kompetenzentwicklungswege: Bildungsgangarbeit in einer dualisierten Ausbildungsvorbereitung. Ergebnisse und Reflexionen aus dem Forschungs- und Entwicklungsprojekt InBig)

,Voraussetzungen und Möglichkeiten der Gestaltung gemeinsamen Lernens für Jugendliche mit sonderpädagogischem Förderbedarf im Bereich Lern- und Entwicklungsstörungen' im Auftrag des Ministeriums für Schule und Weiterbildung des Landes Nordrhein-Westfalen - Kremer, H.-Hugo; Kückmann, Marie-Ann; Sloane, Peter F. E.; Zoyke, A.

Praxisformate in der Ausbildungsvorbereitung - Beutner, Marc; Eickhoff, A.; Kremer, H.-Hugo (Individuelle Kompetenzentwicklungswege: Bildungsarbeit in einer dualisierten Ausbildungsvorbereitung. Ergebnisse und Reflexionen aus dem Forschungs- und Entwicklungsprojekt InBig)

Kollegiale Weiterbildung. Entwicklung, Qualifizierung und Rollenverschärfung für Nachwuchsführungskräfte an Berufskollegs - Kundisch, Heike; Kremer, H.-Hugo (Individuelle Kompetenzentwicklungswege: Bildungsarbeit in einer dualisierten Ausbildungsvorbereitung. Ergebnisse und Reflexionen aus dem Forschungs- und Entwicklungsprojekt InBig)

Multiprofessionelle Teamarbeit - Notwendigkeit und (schleichende) Veränderung von Berufskollegs - Kückmann, Marie-Ann; Kremer, H.-Hugo (Individuelle Kompetenzentwicklungswege: Bildungsarbeit in einer dualisierten Ausbildungsvorbereitung. Ergebnisse und Reflexionen aus dem Forschungs- und Entwicklungsprojekt InBig)

Auf dem Wege zur Qualität in der Ausbildungsvorbereitung - Einblicke in Prozesse zur Entwicklung und Implementation innovativer Konzepte - Kranert, T.; Kremer, H.-Hugo (Individuelle Kompetenzentwicklungswege: Bildungsarbeit in einer dualisierten Ausbildungsvorbereitung. Ergebnisse und Reflexionn aus dem Forschungs- und Entwicklungsprojekt InBig)

Entwicklung von Berufskollegs - Handlungsfelder, Herausforderungen und Unterstützungsbedarf von Nachwuchsführungskräften in der Beruflichen Bildung - Kremer, H.-Hugo; Kundisch, Heike; Schreiner, K. (Individuelle Kompetenzentwicklungswege: Bildungsgangarbeit in einer dualisierten Ausbildungsarbeit. Ergebnisse und Reflexionen aus dem Forschungs- und Entwicklungsprojekt InBig)

Connecting In-Body Nano Communication with Body Area Networks: Challenges and Opportunities of the Internet of Nano Things - Dressler, Falko; Fischer, Stefan (Elsevier Nano Communication Networks)
Nano-communication is considered to become a major building block for many novel applications in the health care and fitness sector. Given the recent developments in the scope of nano machinery, coordination and control of these devices becomes the critical challenge to be solved. In-Body Nano-Communication based on either molecular, acoustic, or RF radio communication in the terahertz band supports the exchange of messages between these in-body devices. Yet, the control and communication with external units is not yet fully understood. In this paper, we investigate the challenges and opportunities of connecting Body Area Networks and other external gateways with in-body nano-devices, paving the road towards more scalable and efficient Internet of Nano Things (IoNT) systems. We derive a novel network architecture supporting the resulting requirements and, most importantly, investigate options for the simulation based performance evaluation of such novel concepts. Our study is concluded by a first look at the resulting security issues considering the high impact of potential misuse of the communication links.

Towards Communication Strategies for Platooning: Simulative and Experimental Evaluation - Segata, Michele; Bloessl, Bastian; Joerer, Stefan; Sommer, Christoph; Gerla, Mario; Lo Cigno, Renato; Dressler, Falko (IEEE Transactions on Vehicular Technology)
Platooning, the idea of cars autonomously following their leaders to form a road train, has huge potentials to improve traffic flow efficiency and, most importantly, road traffic safety. Wireless communication is a fundamental building block - it is needed to manage and to maintain the platoons. To keep the system stable, strict constraints in terms of update frequency and communication reliability must be met. We investigate different communication strategies by explicitly taking into account the requirements of the controller, exploiting synchronized communication slots as well as transmit power adaptation. As a baseline, we compared the proposed approaches to two state of the art adaptive beaconing protocols that have been designed for cooperative awareness applications, namely ETSI DCC and DynB. Our simulation models have been parameterized and validated by means of real-world experiments. Our results demonstrate that the combination of synchronized communication slots with transmit power adaptation is perfectly suited for cooperative driving applications, even in very crowded freeway scenarios.

Erleben Schulischer Wirklichkeit - Schulische Langeweile aus Sicht von Jugendlichen an Berufskollegs - Dirksmeier, V.; Gonsior, R.; Kremer, H.-Hugo (Individuelle Kompetenzentwicklungswege: Bildungsarbeit in einer dualisierten Ausbildungsvorbereitung. Ergebnisse und Reflexionen aus dem Forschungs- und Entwicklungsprojekt InBig)

Kein Ende...vor dem Anfang einer weiteren Professionalisierung der Bildungsarbeit - Kremer, H.-Hugo (Individuelle Kompetenzentwicklungswege: Bildungsarbeit in einer dualisierten Ausbildungsvorbereitung. Ergebnisse und Reflexionen aus dem Forschungs- und Entwicklungsprojekt InBig)

Interference of surface plasmons and Smith-Purcell emission probed by angle-resolved cathodoluminescence spectroscopy - Yamamoto, Naoki; Javier García de Abajo, F.; Myroshnychenko, Viktor (Physical Review B)
We investigate the interplay between geometrical lattice resonances and surface plasmons mediating the emission of Smith-Purcell visible light via angle-resolved cathodoluminescence spectroscopy. We observe strong modulations in the dispersion curves of Smith-Purcell radiation (SPR) when they intersect the surface plasmons of silver gratings using a 200-kV transmission electron microscope. The decay of the plasmons away from the grating is directly probed by controlling the electron-beam position relative to the sample surface with nanometer precision. Our measurements are in excellent agreement with numerical simulations, clearly revealing the presence of characteristic Fano profiles resulting from the interference of the light continuum and the discrete plasmon states for each direction of emission. The intensity anomaly in the SPR emission pattern can be well explained from the geometrical consideration of the intersections between the dispersion planes of the SPR and surface plasmon polariton (SPP). A strong and directional SPR beam can be realized under the condition that the SPR dispersion plane comes in contact with the band edge of the SPP dispersion plane.

Enculturation and development of beginning students - Jenert, Tobias; Postareff, Liisa; Brahm, Taiga; Lindblom-Ylänne, Sari

Pädagogische Hochschulentwicklung: Von der Programmatik zur Implementierung - Brahm, Taiga; Jenert, Tobias; Euler, Dieter
Der Sammelband befasst sich mit einem umfassenden Ansatz zur Verbesserung der Qualität von Lehre und Studium. Mit dem Konzept der pädagogischen Hochschulentwicklung plädieren die AutorInnen dafür, bei der Umsetzung von Veränderungsprojekten die verschiedenen Ebenen der Hochschule zu verschränken. Zum Beispiel sollten Initiativen, die eine Lehrveranstaltung betreffen, idealerweise die (Aus )Wirkungen auf den Ebenen der Studienprogramme und der Organisation berücksichtigen und aktiv gestalten. Die einzelnen Beiträge stellen beispielhafte Initiativen aus unterschiedlichen Disziplinen und Hochschulformen dar und illustrieren, wie die genannten Ebenen in der praktischen Umsetzung verzahnt werden können.

Enculturation and development of beginning students - Jenert, Tobias; Postareff, Liisa; Brahm, Taiga; Lindblom-Ylänne, Sari
Starting with this issue, the ZFHE will publish one English-speaking edition per year on a topic of international interest, in order to disseminate German-language research results beyond our borders and to encourage discussion in an international context. This first English-language edition focuses on the experiences and the academic socialization of first-year university students. The articles offer both diagnoses and differentiations in terms of different types of first-year students, as well as highlighting their experiences and development during their introduction to the academic environment and examining connections between their academic development and the existing educational environment.

The self-fulfilling prophecy of fear of academic failure - Brahm, Taiga; Jenert, Tobias; Wagner, Dietrich
Academic success in Higher Education is influenced by a number of different factors. This paper tackles the question if the individual levels of motivation, anxiety, enjoyment and self-efficacy, measured immediately before entering university, influence the probability of academic success. Former studies have shown an influence of the high school grade, the learning environment and motivational variables. They do not investigate, however, the individual levels of the mentioned constructs before the beginning of the studies. This research was conducted at the University of St. Gallen/Switzerland. The sample includes 695 first-year students who provided information about the individual level of the mentioned constructs. Descriptive statistics show that on average the students are highly motivated, have a high level of self-efficacy and are looking forward to their studies before their beginning. Yet, there are students who have a high level of fear of failure in the study in spite of their high motivation and self-efficacy. A logistic regression shows that there is a significant effect of fear of failure on the probability of study success. This paper shows that fear of failure can increase the probability of academic failure and thus become a self-fulfilling prophecy. It confirms fear as an important factor for academic success. Furthermore, other important factors for academic success, for example the high school grade, could be confirmed in this study
Keywords: Quantitative methods; Student learning; Emotion and Cognition; Social sciences; Higher education; Motivation and Emotion; Fear of Failure

A person-centred approach to students' transition into Higher Education - Brahm, Taiga; Wagner, Dietrich; Jenert, Tobias
A highly selective first study phase in many Swiss study programs leads to a rather competitive climate among students. However, the atmosphere at the university is an important factor for students' transition into Higher Education. An important question in this context is whether students' are equipped with different dispositions influencing how they cope with this transition. Other research has already shown that different groups of students can be identified regarding their student behavior. Yet, so far little is known about patterns of variables characterizing students, transitioning successfully. The paper takes advantage of a person-centered approach, i.e. the latent-class analysis, which makes it possible to identify groups of individuals, sharing common attributes. The research was conducted as a longitudinal study during their first year at a Swiss university. The return rate was about 67%, with 820 utilizable questionnaires at t1. Based on the analysis of students' anxiety, intrinsic motivation and self-efficacy, three distinct classes of students could be identified. The first class can be called the "highly motivated and self-confident" students. The second class is characterized by the same pattern, however, on a more intermediate level and the last class can be described as the "least motivated and most anxious" group of students. This study contributes to research and theory on students' transition into higher education and could be a first hint that students' experiences of this transition can vary substantially.
Keywords: Quantitative methods; Self-efficacy; Higher education; Motivation and Emotion